2004
DOI: 10.1128/jcm.42.11.5109-5120.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Human Pathogenic Members of the Fusarium oxysporum Complex Inferred from Multilocus DNA Sequence Data and Amplified Fragment Length Polymorphism Analyses: Evidence for the Recent Dispersion of a Geographically Widespread Clonal Lineage and Nosocomial Origin

Abstract: Fusarium oxysporum is a phylogenetically diverse monophyletic complex of filamentous ascomycetous fungi that are responsible for localized and disseminated life-threatening opportunistic infections in immunocompetent and severely neutropenic patients, respectively. Although members of this complex were isolated from patients during a pseudoepidemic in San Antonio, Tex., and from patients and the water system in a Houston, Tex., hospital during the 1990s, little is known about their genetic relatedness and popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(185 citation statements)
references
References 38 publications
5
171
3
Order By: Relevance
“…Total DNA was extracted from 20 mg of lyophilized mycelia using the Wizard Magnetic DNA Purification System for Food (Promega, Mannheim, Germany) according to the manufacturer's instructions. The ITS region was amplified using ITS1-F (5′-TCCGTAG GTGAACCTGCGG-3′) and ITS4-R (5′-TCCTCCGC TTATTGATATGC-3′) primers (White et al 1990), while the tef1α was amplified using EF-1 (5′-ATGGGTAA GGARGACAAGAC-3′), EF-2 (5′-GGARGTACCA GTSATCATG-3′) primers (O'Donnell et al 2004) and EF1-728F(5′-CATCGAGAAGTTCGAGAAGG-3′), EF1-986R (5′-TACTTGAAGGAACCCTTACC-3′) primers for Trichoderma specific isolates (Carbone and Kohn 1999). The ß-tubulin region was amplified using Bt2a (5′-GGTAACCAAATCGGTGCTGCTTTC-3′) and Bt2b (5′-ACCCTCAGTGTAGTGACCCTTGGC-3′) primers (Glass and Donaldson 1995).…”
Section: Isolation Of Endophytic Fungimentioning
confidence: 99%
“…Total DNA was extracted from 20 mg of lyophilized mycelia using the Wizard Magnetic DNA Purification System for Food (Promega, Mannheim, Germany) according to the manufacturer's instructions. The ITS region was amplified using ITS1-F (5′-TCCGTAG GTGAACCTGCGG-3′) and ITS4-R (5′-TCCTCCGC TTATTGATATGC-3′) primers (White et al 1990), while the tef1α was amplified using EF-1 (5′-ATGGGTAA GGARGACAAGAC-3′), EF-2 (5′-GGARGTACCA GTSATCATG-3′) primers (O'Donnell et al 2004) and EF1-728F(5′-CATCGAGAAGTTCGAGAAGG-3′), EF1-986R (5′-TACTTGAAGGAACCCTTACC-3′) primers for Trichoderma specific isolates (Carbone and Kohn 1999). The ß-tubulin region was amplified using Bt2a (5′-GGTAACCAAATCGGTGCTGCTTTC-3′) and Bt2b (5′-ACCCTCAGTGTAGTGACCCTTGGC-3′) primers (Glass and Donaldson 1995).…”
Section: Isolation Of Endophytic Fungimentioning
confidence: 99%
“…Recently, at least 300 phylogenetically distinct species were estimated (O'Donnell et al, 2015). O'Donnell et al (2004O'Donnell et al ( , 2007 and Zhang et al (2006) reported that fusaria pathogenic to humans and other animals belong to either the FSSC or FOSC clade. In light of the conclusion by Dupont et al (2007) regarding the Lascaux Cave, we suggested that most TT and KT fusaria in the FSSC clade 3 were also deeply involved in the deterioration of the murals .…”
Section: -1 Fusarium Solani Species Complex (Fssc) Cladementioning
confidence: 99%
“…Within formae speciales, subdivision into races has also been described based on the ability of distinct strains to infect different varieties of a plant host species (O'Donnell et al, 2009). Fusarium oxysporum strains that can cause infection in humans and animals have also been described which cause high mortality in immunodeprived patients (O'Donnell et al, 2004). Although morphological distinction of F. oxysporum from other species of the genus is attainable, infra-specific identification with such method is not feasible.…”
Section: Introductionmentioning
confidence: 99%